Iowa RBA, September 18, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for September 18, 1995. Highlights of the update include sightings of Yellow Rail, Mississippi Kite, White Ibis, Red-necked Phalarope and a Snowy Egret. Epson - sheet feed/flatbed